The Influence Of Leadership Style And Work Motivation On Performance Of Employees (Case Study of the Office of Communication, Informatics, Statistics and Encoding, Luwu Regency - Devi Satia; Muh Yusuf Q; Suhardi M. Anwar (Jurnal Mantik, 2022)
This study aims to determine: (1) Describe the performance of employees in the Department of Communications and Information-SP Luwu Regency (2) The influence of leadership style and work motivation on employee performance at the Department of Communication and Information-SP Luwu Regency. (2) The Influence of Work Motivation on Employee Performance at the Department of Communication and Information-SP Luwu Regency. This research is a correlation research with multiple regression design. The population in this study were all employees at the Department of Communication and Information-SP Luwu Regency. The sample in this study were civil servants and non-civil servants of the Ministry of Communication and Information-SP Kab. Luwu with a total of 70 people. Collection data use information field which has tested validity and its reliability. Technique analysis data y and g used on study this is analysis regression multiple. As a result of the study using a significance level of 5 %, it was found that (1) leadership style had a positive and significant effect on employee performance at the Department of Communication and Informatics-SP Luwu Regency, = 0.750 *** (*** p <0.05; p = 0.000) with style donation . Leadership on employee performance (?R) 0,523 ( 2 ) work motivation has a positive and significant effect on employee performance at the Ministry of Communication and Informatics-SP, = 0.763 *** (*** p <0.05; p = 0.000) with a motivational donation work on employee performance of (?R) 0.533. In conclusion, g aya leadership give impact big in motivate employee for increase performance. Suggestion y and g could given is so that para leader more deep f persuasion lead the organization for the sake of heighten performance employees in an effort to achieve organizational goals.